Preparation method and application of large-size two-dimensional cadmium selenide nanosheet
Large-size two-dimensional cadmium selenide nanosheets were prepared by a mixed heating method using cadmium acetate and selenium powder as solutes. This method solves the problems of high cost and harsh reaction conditions in existing technologies, and achieves low-cost and high-efficiency nanosheet preparation, thereby improving photocatalytic and biosensing performance.
Patent Information
- Application Number
- CN202311020515.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-10-24
- Estimated Expiration
- 2043-08-15
AI Technical Summary
Existing methods for synthesizing two-dimensional cadmium selenide nanosheets use expensive selenourea as a selenium precursor, and the reaction conditions are harsh, the synthesis time is long, and the steps are complicated, making it difficult to achieve industrial application.
Large-sized two-dimensional wurtzite-type cadmium selenide nanosheets were prepared by mixing cadmium acetate and selenium powder as solutes and amine as solvent, followed by heating and controlling the reaction time and temperature. This method avoids high-temperature and high-pressure operation and selects suitable raw materials and conditions.
This method enables the convenient preparation of cadmium selenide nanosheets, improves product performance, and provides excellent optical properties. These nanosheets can be widely used in photocatalysis and biosensing, and are low in cost and have a wide range of applications.
Smart Images

Figure CN117023527B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the field of inorganic semiconductor material synthesis, and particularly relates to a preparation method and application of large-size two-dimensional cadmium selenide nanosheet. BACKGROUND
[0002] At present, in the synthesis of two-dimensional wurtzite cadmium selenide nanosheet, most of the selenium urea with high cost is used as the selenium precursor, which greatly limits the industrial application prospect. In the synthesis of cadmium selenide nanosheet using selenium powder as raw material, most of the reaction conditions are harsh, high temperature, and the steps are complicated, such as the reaction temperature is more than 200 DEG C, and the cadmium precursor needs to pass through stirring, controlled speed dropping, filtration, drying and other processes, the synthesis time is long, and the difficulty is great.
[0003] The cadmium acetate and selenium powder are selected as solutes, amine is used as a solvent, and after being uniformly mixed and heated, the two-dimensional wurtzite cadmium selenide nanosheet with ultraviolet absorption peak of 429nm-518nm can be controllably synthesized. By adjusting the reaction time and temperature, two kinds of two-dimensional wurtzite cadmium selenide nanosheet with different thickness and different ultraviolet absorption wavelength can be obtained, and the two-dimensional wurtzite cadmium selenide nanosheet has a large-size structure with a short side of 130-150nm and a long side of 1-2um. The convenient preparation method of cadmium selenide nanosheet is obtained by controlling the reaction conditions, avoiding high temperature and high pressure operation, and selecting suitable raw materials, the related problems existing in the synthesis of cadmium selenide nanosheet are solved, and the performance of the product is improved. SUMMARY
[0004] The application solves the above technical problems in the prior art, and provides a preparation method and application of large-size two-dimensional wurtzite cadmium selenide nanosheet.
[0005] The technical scheme of the application is as follows:
[0006] A preparation method of large-size two-dimensional cadmium selenide nanosheet, comprising the following steps:
[0007] Step 1, ultrasonic treatment and heating treatment of cadmium acetate in n-octylamine solution to synthesize cadmium precursor solution;
[0008] Step 2, ultrasonic treatment of selenium powder in n-octylamine solution, addition of a reducing agent for reduction to synthesize selenium precursor solution;
[0009] Step 3, mixing of the cadmium precursor solution and the selenium precursor solution, standing, degassing, and heating and sealing reaction after inert gas is introduced;
[0010] Step 4, centrifugal washing to obtain the product;
[0011] The molar ratio of the selenium powder to the cadmium acetate is 1.6:1-2:1; and the molar ratio of the reducing agent to the selenium powder is 1:1-2:1.
[0012] Preferably, in step 1, 0.2-0.4 mmol of cadmium acetate is added to 7-11 ml of n-octylamine solution, and ultrasonic treatment and heating treatment are performed to synthesize the cadmium precursor solution.
[0013] Preferably, in step 2, 0.4-0.6 mmol of selenium powder is added to 2-9 ml of n-octylamine solution, ultrasonic treatment is performed, a reducing agent is added for reduction, and the selenium precursor solution is synthesized; more preferably, the amount of the n-octylamine solution is 2-4 ml or 6-9 ml.
[0014] Preferably, in step 2, the reducing agent is sodium borohydride or lithium triethylborohydride; more preferably, the reducing agent is 0.4-1.0 mmol of sodium borohydride or 0.6-1.2 mmol of lithium triethylborohydride.
[0015] Preferably, in step 1, ultrasonic treatment is performed for 10 mins, and heating treatment is performed at 60°C for 30 mins to synthesize the cadmium precursor solution.
[0016] Preferably, in step 3, the temperature for heating and sealing reaction is 50-100°C; more preferably, the temperature for heating and sealing reaction is 50-70°C or 75-100°C.
[0017] Preferably, in step 3, after mixing the cadmium precursor solution and the selenium precursor solution, the mixture is left still at room temperature for 24 hours, degassed for 5-10 mins, and inert gas is introduced for 5-10 mins, and heating and sealing reaction is performed for 20-48 h, and natural cooling is performed to room temperature.
[0018] Preferably, in step 4, the supernatant is removed by centrifugation, and the precipitate is washed with a mixed solution of toluene and tri-n-octylphosphine, a mixed solution of toluene and ethanol, and toluene, respectively.
[0019] Preferably, in the mixed solution of toluene and tri-n-octylphosphine, the volume ratio of toluene to tri-n-octylphosphine is 10:1-20:1.
[0020] Preferably, in the mixed solution of toluene and ethanol, the volume ratio of toluene to ethanol is 4:1-3:1.
[0021] Preferably, the product is dispersed in a toluene solution and stored in a sealed manner at room temperature.
[0022] Preferably, in step 4, the centrifugation condition is 8000-12000 r / min for 45-90 s.
[0023] The prepared cadmium selenide nanosheet can be used for photocatalytic reduction of CO2. Compared with the commercial TIO2 under the same photocatalytic reaction condition, the prepared cadmium selenide nanosheet has more excellent photocatalytic performance.
[0024] Compared with the prior art, the present application has the following advantages,
[0025] The present application avoids high temperature and high pressure operation by controlling the reaction condition, and selects suitable raw materials, so as to obtain a convenient preparation method of cadmium selenide nanosheet, solve the related problems in the synthesis of cadmium selenide nanosheet, and improve the performance of the product. The cadmium selenide nanosheet prepared by the present application has excellent optical performance in addition to different thicknesses obtained by changing the temperature and reaction time, and can be widely used in the fields of biological sensing and photocatalysis. In addition, the preparation method of the present application has low cost and wide application range, is a preparation method worthy of popularization, and has broad market prospect. BRIEF DESCRIPTION OF DRAWINGS
[0026] Figure 1 Figure 1 a is a transmission electron microscope image of 4-W-CdSe NPLs in Example 2; Figure 1 b is a transmission electron microscope image of 3-W-CdSe NPLs in Example 1;
[0027] Figure 2 X-ray diffraction patterns of 3-W-CdSe NPLs and 4-W-CdSe NPLs;
[0028] Figure 3 UV-Vis spectra of toluene dispersions of 3-W-CdSe NPLs and 4-W-CdSe NPLs prepared in Example 1 and Example 2, measured on an Australian Agilent Cary 5000 UV-Vis-NIR spectrometer;
[0029] Figure 4 Under the same light condition, the photocatalytic performance of 3-W-CdSe NPLs, 3-W-CdSe NPLs mixed with gold particles and commercial TIO2 in the photocatalytic reduction of CO2 in the gas-solid phase was compared. DETAILED DESCRIPTION
[0030] Example 1
[0031] (1) A proper amount of 0.3mmol cadmium acetate was added to 8ml n-octylamine solution, ultrasonic was performed for 10mins, and heating was performed at 60℃ for 30mins, and after the cadmium acetate was completely dissolved, a transparent cadmium precursor solution was formed;
[0032] (2) 0.55 mmol of selenium powder was added to 3 ml of n-octylamine solution, ultrasonicated for 10 min, and 0.55 mmol of sodium borohydride was added to synthesize a purple-black selenium precursor solution;
[0033] (3) The cadmium precursor solution and the selenium precursor solution were then poured into a 50 ml single-necked round-bottom flask and mixed. The mixture was then sealed and left to stand at room temperature for 24 hours. The mixture was then degassed for 10 minutes, nitrogen was introduced for 10 minutes, and the mixture was sealed and reacted at 60°C for 40 hours, and then cooled naturally to room temperature.
[0034] (4) The product was transferred to a 50 ml centrifuge tube and centrifuged at 8000 r / min for 60 s. The supernatant was removed and washed with 12 ml of a mixture of toluene and trioctylphosphine (volume ratio 15:1). The above centrifugation operation was repeated and 12 ml of a mixture of toluene and ethanol (volume ratio 3:1) and 8 ml of toluene were added for washing once each. The final precipitate was dispersed in 5 ml of toluene solution and turned yellow-green. The product was sealed and stored at room temperature. The product was a two-dimensional wurtzite-type cadmium selenide nanosheet with UV absorption peaks of 429 nm and 456 nm. It was recorded as 3-W-CdSe NPLs.
[0035] like Figure 1 As shown in b, the synthesized two-dimensional zincite-type cadmium selenide nanosheets have a large-scale structure with a short side of 130-150nm and a long side of 1-2μm.
[0036] Example 2
[0037] (1) Add an appropriate amount of 0.25 mmol of cadmium acetate to 8 ml of n-octylamine solution, ultrasonicate for 10 min, and heat at 60°C for 30 min. After the cadmium acetate is completely dissolved, a transparent cadmium precursor solution is formed.
[0038] (2) 0.5 mmol of selenium powder was added to 3 ml of n-octylamine solution, ultrasonicated for 10 min, and 1 mmol of lithium triethylborohydride was added to synthesize a purple-black selenium precursor solution;
[0039] (3) The cadmium precursor solution and the selenium precursor solution were then poured into a 50 ml single-necked round-bottom flask and mixed. The mixture was then sealed and left to stand at room temperature for 24 hours. The mixture was then degassed for 10 minutes, nitrogen was introduced for 10 minutes, and the mixture was sealed and reacted at 80°C for 36 hours. The mixture was then heated to 100°C for annealing for one hour and naturally cooled to room temperature.
[0040] (4) The product was taken out and transferred into a 50-ml centrifuge tube, and the supernatant was removed by centrifugation at 10,000 r / min for 45 s. The precipitate was washed with 10 ml of a mixture of toluene and tri-octylphosphine (volume ratio 20:1), and the above centrifugation was repeated. The precipitate was washed once with 10 ml of a mixture of toluene and ethanol (volume ratio 4:1) and once with 8 ml of toluene, respectively. The final precipitate was dispersed in 10 ml of toluene and stored at room temperature in a sealed state. The product was two-dimensional wurtzite-type cadmium selenide nanosheet with ultraviolet absorption peaks at 485 nm and 518 nm, and was recorded as 4-W-CdSe NPLs.
[0041] As shown in FIG. 4A, the synthesized two-dimensional wurtzite-type cadmium selenide nanosheet has a large-size structure with a short side of 130-150 nm and a long side of 1-2 μm. Figure 1
[0042] As shown in FIG. 4B, there is a significant difference in diffraction angle between 3-W-CdSe NPLs and 4-W-CdSe NPLs, and there is also a small amount of negligible by-product additional peak. Figure 2 As shown in FIG. 4C, under the same photocatalytic reaction conditions, the photocatalytic performance of 3-W-CdSe NPLs, 3-W-CdSe NPLs Au (3-W-CdSe NPLs mixed with gold nanoparticles at a mass ratio of 100:1), and commercial TIO2 was compared, respectively. The results show that the CO yield of 3-W-CdSe NPLs is equivalent to that of commercial TIO2, and the CH4 yield is better than that of the latter. After mixing with 3-W-CdSe NPLs Au, the CO yield and CH4 yield are much higher than those of commercial TIO2.
[0043] Figure 4 Example 3
[0044] (1) A proper amount of 0.25 mmol of cadmium acetate was added to 8 ml of n-octylamine solution, and ultrasonic treatment was performed for 10 mins. The solution was heated at 60°C for 30 mins, and a transparent cadmium precursor solution was formed after the complete dissolution of cadmium acetate;
[0045] (2) 0.5 mmol of selenium powder was added to 3 ml of n-octylamine solution, and ultrasonic treatment was performed for 10 mins. Then, 0.5 mmol of sodium borohydride was added to synthesize a purple-black selenium precursor solution;
[0046] (3) Then, the cadmium precursor solution and the selenium precursor solution were poured into a 50-ml single-mouth round-bottom flask and mixed. After being left still at room temperature in a sealed state for 24 hours, the solution was degassed for 10 mins, nitrogen was introduced for 10 mins, and the solution was sealed and reacted at 100°C for 20 h, and then naturally cooled to room temperature;
[0047] (4) The product was taken out and transferred into a 50-ml centrifuge tube, and the supernatant was removed by centrifugation at 10,000 r / min for 45 s. The precipitate was washed with 10 ml of a mixture of toluene and tri-octylphosphine (volume ratio 20:1), and the above centrifugation was repeated. The precipitate was washed once with 10 ml of a mixture of toluene and ethanol (volume ratio 4:1) and once with 8 ml of toluene, respectively. The final precipitate was dispersed in 10 ml of toluene and stored at room temperature in a sealed state. The product was two-dimensional wurtzite-type cadmium selenide nanosheet with ultraviolet absorption peaks at 485 nm and 518 nm, and was recorded as 4-W-CdSe NPLs.
[0048] (4) The product was taken out and transferred into a 50 ml centrifuge tube, and centrifuged at 10000 r / min for 45 s to remove the supernatant. The precipitate was washed with 10 ml of a mixture of toluene and tri-octylphosphine (volume ratio 15:1), and the above centrifugation was repeated. The precipitate was washed once with 10 ml of a mixture of toluene and ethanol (volume ratio 4:1) and 10 ml of toluene, respectively. The final precipitate was dispersed in 10 ml of toluene and stored at room temperature in a sealed state. The product was two-dimensional wurtzite-type cadmium selenide nanosheet with ultraviolet absorption peaks at 485 nm and 518 nm, and was recorded as 4-W-CdSe NPLs.
[0049] Example 4
[0050] The same as in Example 1, except that the step (3) was modified to be reacted at 56 ℃ for 48 h in a sealed state, and the product was two-dimensional wurtzite-type cadmium selenide nanosheet with ultraviolet absorption peaks at 429 nm and 456 nm. It was recorded as 3-W-CdSe NPLs.
[0051] Example 5
[0052] The same as in Example 1, except that the molar ratio of selenium source to cadmium source was modified to be 1.6:1, the step (3) was reacted at 50 ℃ for 48 h in a sealed state, and the volume ratio of toluene to tri-octylphosphine was 20:1, and the volume ratio of toluene to ethanol was 3:1. The product was two-dimensional wurtzite-type cadmium selenide nanosheet with ultraviolet absorption peaks at 429 nm and 456 nm, and had a large size structure with a short side of 130-150 nm and a long side of 1-2 μm.
[0053] Comparative Example
[0054] The same as in Example 1, except that the amount of sodium borohydride in step (2) was modified to be 0.3 mmol. The product had the following effects: after the reaction was completed, a large amount of Se powder still existed, and the solution was black and turbid. After washing, the product had multiple impurity peaks in addition to the ultraviolet absorption peaks at 429 nm and 456 nm.
[0055] The same as in Example 2, except that the amount of selenium powder in step (2) was modified to be 0.3 mmol. The product had the following effects: after the reaction was completed and washed, the product had ultraviolet absorption peaks at 429 nm, 456 nm, 485 nm and 518 nm, and contained 3-W-CdSe NPLs, 4-W-CdSe NPLs or was not completely converted into 4-W-CdSe NPLs.
[0056] It should be noted that the above examples are only the preferred embodiments of the present application, and do not limit the protection scope of the present application. Any equivalent substitutions or replacements made on the basis of the above are within the protection scope of the present application.
Claims
1. A method for preparing large-size two-dimensional cadmium selenide nanosheets, characterized in that, The method comprises the following steps: Step 1, adding cadmium acetate into n-octylamine solution, ultrasonic treatment and heating treatment to synthesize cadmium precursor solution; Step 2, adding selenium powder into n-octylamine solution, ultrasonic treatment, adding reducing agent to reduce to synthesize selenium precursor solution; the reducing agent is sodium borohydride or lithium triethylborohydride; The molar ratio of the selenium powder to cadmium acetate is 1.6:1-2:1; the molar ratio of the reducing agent to selenium powder is 1:1-2:1; Step 3, mixing the cadmium precursor solution and the selenium precursor solution, standing, degassing, and then heating and sealing reaction after inert gas is introduced; the heating and sealing reaction temperature is 50-100℃; Step 4, centrifugal washing to obtain the product.
2. The preparation method according to claim 1, wherein, In the step 1, 0.2-0.4mmol cadmium acetate is added into 7-11ml n-octylamine solution, ultrasonic treatment and heating treatment to synthesize cadmium precursor solution; In the step 2, 0.4-0.6mmol selenium powder is added into 2-9ml n-octylamine solution, ultrasonic treatment, and adding reducing agent to reduce to synthesize selenium precursor solution.
3. The production method according to claim 1, wherein In the step 1, ultrasonic treatment is performed for 10 minutes, and then the solution is heated at 60℃ for 30 minutes to synthesize cadmium precursor solution.
4. The production method according to claim 1, wherein In the step 3, after the cadmium precursor solution and the selenium precursor solution are mixed, standing is performed at room temperature for 24 hours, degassing is performed for 5-10 minutes, inert gas is introduced for 5-10 minutes, heating and sealing reaction is performed for 20-48 hours, and natural cooling is performed to room temperature.
5. The production method according to claim 1, wherein In the step 4, supernatant is removed by centrifugation, and the precipitate is washed with a mixed solution of toluene and tri-octylphosphine, a mixed solution of toluene and ethanol, and toluene.
6. The preparation method according to claim 5, wherein The volume ratio of toluene to tri-octylphosphine in the mixed solution is 10:1-20:1; the volume ratio of toluene to ethanol in the mixed solution is 4:1-3:
1.
7. The production method according to claim 1, wherein In the step 4, the centrifugation condition is: 8000-12000r / min, and the time is 45-90s.
8. Application of cadmium selenide nanosheets prepared by the preparation method according to any one of claims 1-7 in photocatalytic reduction of CO2.
Citation Information
Patent Citations
Controllable synthetic method of two-dimensional wurtzite-form cadmium selenide nanomaterials
CN105800570A
Preparation method of blue-light sphalerite CdSe / CdS nuclear crown structure nano sheet
CN110127631A